PENYULUHAN TENTANG PERSONAL HYGIENE DAN KECACINGAN MURID SEKOLAH DASAR DI SEKOLAH DASAR NEGERI 104243 KABUPATEN DELI SERDANG LUBUK PAKAM - Fitri Ramadani Harahap; Nora Ervina Sembiring; Darwin Tamba (JURNAL PENGMAS KESTRA (JPK), 2021)
Dewormy is a chronic endemic disease caused one or more worms that enter into the human body, with the highest prevalence found in children. Dewormy can be affected by several factors, namely environmental factors, personal hygiene (cleanliness), age , and gender . Personal Hygiene is an act to maintain the cleanliness of one's health and well-being, both physical and psychic. The research was carried out with methods, selection of cross-sectional samples performed 3 stages, namely with proportional stratified sampling, purposive sampling and simple random sampling. A sample of 59 respondents. Analyzed data with chi-square statistical test of the significance level (Ã¡) of 0.05. The results showed that out of 59 study subjects, know to students with good personal hygiene status as many 18 people ( 30,5 % ), and less well as many as 22 people ( 37,3 %). Laboratory results for the category of positive Dewormy amounted to 44 people ( 75,5 % ) and the negative category Dewormy is equal to 15 people ( 24,7 % ) .